Investigation of NaOH concentration effect in injected fuel on the performance of passive direct methanol alkaline fuel cell with modified cation exchange membrane. (1st January 2016) - Alipour Najmi, Ali; Rowshanzamir, Soosan; Parnian, Mohammad Javad
Abstract: A passive DMAFC (direct methanol alkaline fuel cell) using CEM (cation exchange membrane) is operated and compared to passive DMFC (direct methanol fuel cell) which is operated in acidic condition. Nafion117 membrane is applied as solid polymer electrolyte membrane for both the alkali and acidic conditions. Sodium conducting membrane is prepared by dipping Nafion117 membrane into NaOH solution. The Nafion117/NaOH membrane exhibits higher mechanical and thermal properties than pristine Nafion117. The methanol crossover rate through membrane is also measured using an electrochemical technique and the results reveal that the cell using sodium conducting membrane has lower permeability to methanol than that in the cell using proton exchange membrane. Passive DMAFC using a sodium conducting membrane exhibits a higher OCV (open circuit voltage) and superior cell performance than those in passive DMFC using a proton conducting membrane. The cell performance of DMAFC is investigated by varying the concentration of methanol and alkali solutions. Single cell performance suggests that passive DMAFC with Nafion117/NaOH membrane can produce a maximum power density which is remarkably higher than that in passive DMFC. Highlights: Proposal of an alkali version of passive DMFC (DMAFC) with cation exchange membrane. Higher peak power density and OCV for passive DMAFC than those for passive DMFC. Investigation of NaOH and MeOH concentration effects on performance of passive DMAFC. Higher peak power density with lower Pt/C catalyst loading for passive DMAFC.